MABBARAZANJI: Tradisi Membaca Kitab Barzanji dalam Upaya Meneladani Kehidupan Nabi Muhammad SAW - Abdul Fattah; Lutfiah Ayundasari (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2021)
Al Barazanji is a prayer containing praises and narrations of the Prophet Muhammad SAW which is usually sung with a distinctive rhythmic tone. The Mabbarazanji tradition in the Bugis community is a form of acculturation of Islamic culture and merges with local customs. The purpose of writer is to try to imitate the content of Al-Barzanji and the implementation of the Mabbarazanji tradition in the daily life of the Bugis people. In this research using methods, among others the method of literature study, scientific articles, and book sources. The author hopes that after this research, it can increase the love of the Bugis people in imitating the characteristics of the Prophet Muhammad and respecting the Mabarazanji tradition as a standard of life that is always attached to our daily lives.